2017
DOI: 10.1634/theoncologist.2017-0230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metastasectomy in the Multimodality Approach for BRAF V600E Metastatic Colorectal Cancer: The Mayo Clinic Experience

Abstract: V600E metastatic colorectal cancer (mCRC) represents an extremely difficult molecular subset of colorectal cancer to treat. To date, this subset remains refractory to standard chemotherapies, prompting extensive clinical investigation regarding novel treatment approaches and targeted modalities. While the use of metastasectomy for expanded wild-type and mutated mCRC has resulted in improved overall survival for select patients, utilization of metastasectomy in patients with V600E mCRC remains controversial. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
0
22
1
2
Order By: Relevance
“…In favor of metastasectomy of BRAF mutants were the findings of the only study to date that directly compared survival in patients who underwent resection of their BRAF tumors vs those who received systemic treatments only. Patients who underwent metastasectomy survived longer, although the difference was not as pronounced as we may have expected (29.1 vs 22.7 months) . Unfortunately, the two patient groups were not matched, and the authors did not report on the baseline characteristics of the two groups and some selection bias was inherent.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In favor of metastasectomy of BRAF mutants were the findings of the only study to date that directly compared survival in patients who underwent resection of their BRAF tumors vs those who received systemic treatments only. Patients who underwent metastasectomy survived longer, although the difference was not as pronounced as we may have expected (29.1 vs 22.7 months) . Unfortunately, the two patient groups were not matched, and the authors did not report on the baseline characteristics of the two groups and some selection bias was inherent.…”
Section: Resultsmentioning
confidence: 80%
“…Lastly, Johnson et al from the Mayo Clinic was the only group that compared long‐term outcomes between surgically and medically treated patients with BRAF‐mutated tumors. They reported on a total of 52 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a small single-center cohort study showed that 21 of 52 patients with BRAF V600E mutant who underwent metastasectomy had longer OS (29.1 vs. 22.7 months) and progression-free survival (13.6 vs. 6.2 months) than the non-metastasectomy cohort. The authors concluded that multimodality therapy incorporating metastasectomy for BRAF V600E metastatic CRC should be considered and might be associated with improved OS in selected patients [24]. Meanwhile, BRAF V600E can be a biomarker for selecting the appropriate chemotherapy regimen [21].…”
Section: Prognostic Determinantsmentioning
confidence: 99%
“…Recently, a small single‐center cohort study showed that 21 of 52 patients with BRAF V600E mutant who underwent metastasectomy had longer OS (29.1 months vs 22.7 months) and PFS (13.6 months vs 6.2 months) compared with the non‐metastasectomy cohort. The authors concluded that multimodality therapy incorporating metastasectomy for BRAF V600E metastatic CRC (mCRC) should be considered and might be associated with improved OS in selected patients . Meanwhile, BRAF V600E can be a biomarker for selecting the appropriate chemotherapy regimen.…”
Section: Biomarkers For Crlmmentioning
confidence: 99%